Effect of environmental temperature and restricted feeding on composition of rabbit milk - Kustos K.; Papp Z.; Szendrö Z.; Bálint A. (2. International Conference on Rabbit Production in Hot Climates, 1999)
Thirty-six NZW lactating rabbit does were divided into 6 groups according to environmental temperature and feed intake. The rabbits kept at 5, 15, 23 and 30oC were fed ad libitum (5A, 15A, 23A, and 30A) but two groups of does kept at 15 oC were fed restricted rations , being fed the same amount of pellet as the intake of the rabbits kept at 23 or 30 oC (15/23R, 15/30R). Milk samples were collected on days 3, 7, 14, 21, 24 and 27 and the composition of pooled milk samples was subjected to chemical analysis.The effect of temperature and feed restriction was negligible.
2. International Conference on Rabbit Production in Hot Climates, 1998/09/07-09, Adana (Turkey)